PEMANFAATAN BIOMAS SAMPAH ORGANIK TERHADAP UJI PERTUMBUHAN DAN HASIL TANAMAN SAWI - Nisak, Fauziatun; Pratiwi, Yeni Ika (JHP17 (Jurnal Hasil Penelitian), 2019)
he condition of the abundance of organic waste in Surabaya's urban environment requires asolution not only concerning the composting process into fertilizers or organic fertilizers, but also how toutilize organic waste biomass in empowering urban land that is narrowly shaped vegetable cultivation thatcontributes to nutrition for the family. This study aims to determine the effect of organic waste biomassfrom the most effective and efficient composting of urban organic waste on the growth and yield of mustardgreens.Based on the results of the study, it can be concluded as follows:1. There is a significant effect of the composition of urban organic fertilizer on the parameters ofgrowth and yield of mustard plants on the variables studied, including: plant length, number ofleaves, root length and fresh weight per plant.2. The highest fresh weight value per plant was achieved by treatment P3 (15% of the weight of theplanting medium) of 313.82 grams as well as effective and efficient treatment, this was alsosupported by growth variables such as plant length, leaf number and root length; althoughstatistically the P3 treatment was different not significantly with treatment P5 (25%) and P7 (35%).Keywords: Organic Waste Biomass, mustard greens.